1977
DOI: 10.1180/minmag.1977.041.319.19
|View full text |Cite
|
Sign up to set email alerts
|

Iron-boracite from the English Zechstein

Abstract: Iron-boracite from the English Zechstein IRON-BORACITE, (Fe, Mg, Mn)aBTO13CI, has been found in nodules in an anhydritic shale that overlies the sylvinite (sylvine-halite rock) of the third Zechstein Evaporite Cycle at the Boulby Mine, Loftus, Saltburn, Cleveland. This is the first record of the mineral in this country. The succession in the type roadway is:Anhydritic shale with the iron-boracite nodule bed near its base; the Shale and NoduleBeds are cross-cut by red sylvine-halite veins from the sylvinite b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Borate minerals reported from Boulby mine include a species first described as "iron boracite" (Milne et al 1977), which was later shown to be trembathite or congolite (Green 2005), boracite and hilgardite (e.g., Green and Freier 1994, 1996,2010), and the rare strontium borate p-veatchite (Tindle 2008). As a result of this study volkovskite, which is abundant in the northernmost area of workings approximately 10 kilometers from the access shaft, szaibélyite, and hydroboracite can be added.…”
Section: Discussionmentioning
confidence: 99%
“…Borate minerals reported from Boulby mine include a species first described as "iron boracite" (Milne et al 1977), which was later shown to be trembathite or congolite (Green 2005), boracite and hilgardite (e.g., Green and Freier 1994, 1996,2010), and the rare strontium borate p-veatchite (Tindle 2008). As a result of this study volkovskite, which is abundant in the northernmost area of workings approximately 10 kilometers from the access shaft, szaibélyite, and hydroboracite can be added.…”
Section: Discussionmentioning
confidence: 99%